Browsing Science Research at the Federal Level in Canada : History, Research Activities, and Publications - Wilks, Brian B. (Book collections on Project MUSE., 2004)
Science Research at the Federal Level in Canada is designed to provide much-needed information about the intertwined relationship between science research and politics at the federal level in Canada. Social, economic, and political imperatives drive the direction and scope of the scientific and technical research conducted by federal agencies, but little is known about the knowledge base of government publications and the literature of Canadian science and technology.Covering the federal departments of Agriculture, Environment (including the Canadian Wildlife Service and the Meteorological Service of Canada), Fisheries and Oceans, and Natural Resources (including the Canadian Forest Service, the Earth Sciences Section, and the Geological Survey of Canada) as well as the National Research Council and Industry Canada, Brian Wilks provides a historical background, list of publications, and description of activities for most of the major science initiatives undertaken at the federal level. He surveys a wide range of government documents and monographic and serial science collections used by both faculty and students. Written primarily for science librarians and students, this comprehensive monograph will prove an invaluable addition to any science library.